Une région, plusieurs mondes, impressions d’une étude de terrain dans la région du Jarí, Amazonie brésilienne, août 2009 - Ana Greising (Confins)
This article is based on a prolonged fieldwork carried out in the Brazilian Amazon region between January and August 2009 for a PhD in geography about the rise and development of the Jarí river region, a trans-border territory between the Amapá and the Pará state. The recent history of this area inextricably connected with the installation in 1967 of an agro-industrial company, the Jari Cellulose S.A., by the American businessman D.K. Ludwig. He had set up a large-scale production of paper pulp on the basis of extensive tree plantations. However, the area was already populated by small communities making a living by gathering forest products and through small-scale subsistence agriculture. With the arrival of the company, the area took a new turn, characterized by new and dynamic economy, but also by considerable social and ecological impacts. Its contradictory effects on the region suspended between development and conservation in the context of the Amazon forest are still notable today. The journey documented in this text is about the last and most remote excursion endeavoured during the fieldwork in the region. It takes us to the communities of the Estrada Nova, a territory at the south-west end of the Jarí Cellulose domain. Here, the majority of the families in the communities live isolated from the company, either in absolute independence or in quiet cooperation with the latter. The following article includes several testimonies of some of the key-characters encountered during the expedition to and across the Estrada Nova.